Nilai spiritual Bimbingan dan Konseling: Studi Kasus: Madrasah Aliyah Nurul Ummah Yogyakarta - S. Latinapa, Moh. Hidayat; Faizah, Nurul (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2018)
This research was conducted to investigate the process of spirituality values in the counselling process carried by counsellors to students of Madrasah Aliyah Nurul Ummah Kota Gede Yogyakarta. The urgency of this study is according to the facts in which show that Guidance and Counselling is considered as something that is scary,shunned and becomes an enemy to students. This condition occurs because the majority of Counselling Guidance in schools are considered as school police, lawyers, guardians of the rules and courts for sanctioned students. This qualitative research was conducted by interviewing and observing counselling teachers at the Madrasah Aliyah Nurul Ummah regarding spirituality values in its implementation. Based on the results of the analysis, Madrasah Aliyah Nurul Ummah has unconsciously practiced spirituality values in the Guidance and Counselling process by conducting classical counselling services such as providing understanding and socialization about Guidance and Counselling, learning motivation, inspirational stories (role models). Besides that, the Madrasah Aliyah Nurul Ummah also teaches values and spirituality by commanding students to read the Asmaul Husna, and dhikr at every morning to strengthen their piety and characteristic.